(NkI)QÃWSKAQ rUSX (B:s)E (NPOSOBIE (B/s - (NgREKOW(B, (Nb(B. (Nd(B.,s; (N~EREPNIN(B, (Nl(B. (Nw(B.,s ((NmOSKWA (B:s (NgOSPOLITIZDAT(B,s, 1953)
(Nu^EBNIK POSWQ]EN ISTORII kIEWSKOJ rUSIs
(NoRIG)QÆNAL ZAPISU ZA POSILANNQMs)E
Keywords: )Qæ(NSTORÆQ uKRAÇNIs)E -- (NkI)QÇWSXKA rUSXs)E; (NOB]INAs; (NM)QÆSTOs)E; (NSUSP)QÆLXNIJ USTRÆJs)E; (NSMERDIs; (N^ELQDXs; (NPOL)QÆTI^NIJ USTRÆJs)E; (NKULXTURAs; (NkI)QÇWSXKA rUSXs)E; (NwOLODIMIRs; (NHRE]ENNQs; (NqROSLAWs; (NW)QÆDNOSINIs)E; (NRUSXKO(B-(NPOLXSXK)QÆs)E; (NRUSXKO(B-(N^ESXK)QÆs)E; (NwOLODIMIRmONOMAHs; (NrUSXKAPRAWDAs